The introduction of new technologies and financial support for the innovational pharmaceutical industry in the veterinary medicine sector based on the development of priority areas of the Ukrainian regions - I. V. Bushuieva; N. M. Borysenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2019)
The purpose of the work was to monitor the level of financing of innovation activities and regional level technologies transfer by regions of Ukraine on the basis of medium-term priority directions of innovation activity of the strategic priority on the national level “Technological renewal and development of the agro-industrial complex” and to realization of regional innovation priorities on the development and introduction of the latest biotechnologies and veterinary security medicines for farm animals.